Impact of Herbal Aphrodisiac Pausinytalia yohimbe (BURANTASHI) on the Morphology of Sperm Cells in Adult Male Wister Rats and Mice - Isaiah, Ibeh Nnanna; Okungbowa, M.A.; Omorodion, N.T.; Nnanna, Ibeh Isaiah (Acta Scientific Pharmaceutical Sciences, 2020)
Burantashi Pausinytalia yohimbe is been used as a local aphrodisiac to enhance sexual activities, it is very common amongst the northern Nigerian men, it is also used in suya preparation. The effect P. yohimbe has on the fertility of man and animals has been discussed, although it enhances the virality as regards sexual performance does it in turn have negative impact on the sperm cell quality and if it does, does it affect the morphology of the sperm cells and what kind of morphological changes do occur. 54 Adult male Wister rats where acclimatized and broken down into study groups with the control group as a model of comparison, they were broken into 6 rats in each group, the P. yohimbe extract where administered orally to the rats at 200mg and 400mg concentrations for 14 days, 28 days and 48 days respectively after which they were sacrificed and the sperm cells where analysed for possible morphological abnormalities. The rats at day 14, 28 and 48 with the increase in concentration and dose, noticeable significant changes (p<0.005) where observed with 200mg and 400mg of day 14, 28 and 48 having significant difference in the abnormal sperm cells as compared with the control groups who where fed water and feed. The abnormal morphology ranged from headless, tailless, short tail, big head and double tail, with the Headless and tailless morphological changes having the highest percentage occurrence. The fact that Burantashi P. yohimbe enhances sexual performance doesn’t mean it has not effect on the sperm cell quality as observed in this study it impacts on the morphological changes observable by their shape, size and density variance from those not orally administered P. yohimbe.
Keywords: Nigeria; ACE: Reproductive Health Innovation; University of Benin; CERHI; Burantshi; Morphology; Aphrodisiac; Pausinytalia Johimbe